Development and Implementation of Location Based Native Mobile Application - Čović, Zlatko; Babić, Dejan (International Journal of Electrical and Computer Engineering Systems, 2014)
This paper presents the development and implementation of a location based native mobile application for smart phones with the Android operating system. It can be used in promotion of some product or brand in the way of mobile games. The application has the administration interface (back-end) for data manipulation of users, administrators, clients and items. The system distinguishes between three levels of users: the main administrator, administrators-customers and users. The paper also describes the concept of the division of mobile applications as well as the advantages and disadvantages of the implementation within each group. The application is tested in real conditions on more devices.